H-2RIIBP (RXR beta) heterodimerization provides a mechanism for combinatorial diversity in the regulation of retinoic acid and thyroid hormone responsive genes. - Marks, M S (1992)
H-2RIIBP (RXR beta) is a member of the nuclear hormone receptor superfamily that activates transcription of MHC class I genes in response to retinoic acid (RA). Using chemical cross-linking, co-immunoprecipitation, gel mobility shift and streptavidin-biotin DNA precipitation assays, we show that H-2RIIBP formed heterodimers with thyroid hormone (T3) and RA receptors (T3R alpha and RAR alpha). H-2RIIBP heterodimer formation required a conserved sub-domain of its C-terminal region, occurred independently of target DNA and was much more efficient than either T3R alpha/RAR alpha heterodimer or H-2RIIBP homodimer formation. Heterodimers displayed enhanced binding to target DNA elements and contacted DNA in a manner distinct from that of homodimers. A functional role for heterodimers in vivo was demonstrated by synergistic enhancement of MHC class I transcription following co-transfection of H-2RIIBP with T3R alpha or RAR alpha. We provide biochemical evidence that H-2RIIBP formed heterodimers with several naturally occurring nuclear proteins. The results suggest that H-2RIIBP, by virtue of its ability to heterodimerize, enhances combinatorial diversity and versatility in gene regulation mediated by nuclear hormone receptors.